Publication Practices in the Argentinian Computer Science Community: A Bibliometric Perspective - Mateos Diaz, Cristian Maximiliano (2015)
The Computer Science (CS) community has been discussing, for some time now, the role of conferences as publication venues. In this regard, computer scientists claim to have a long-standing tradition in publishing their research results in conferences, which are also recognized as being different to events in other disciplines. This practice, however, contrasts with journal driven publication practices which are the prevailing academic standard. Consequently, the assessment of the quality of CS conferences with respect to journals is a recurrent topic of discussion within evaluation boards in charge of judging researchers’ performance. Even when agreements are feasible inside the discipline, they are often subject to the scrutiny in the context of multi-disciplinary evaluation boards—usually ruled by standard bibliometrics—in which CS researchers compete for obtaining scholarships, positions and funding. The Argentinian CS community is not an exception in this respect. In this paper, we present a study of the publication practices of the Argentinian CS community, their evolution over time and, more importantly, the impact they achieved in terms of citations. The findings of this study are good basis for understanding the publishing practices of our community, promoting future discussions as well as supporting the community positions regarding these issues.